2021
DOI: 10.3390/jcm10102208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Psychological Biomarkers on Therapeutic Adherence by Patients with Non-Alcoholic Fatty Liver Disease: A Moderated Mediation Model

Abstract: Our aim was to analyze whether depressive symptoms mediated the association between physical quality of life (QoL) and adherence to physical activity in patients with non-alcoholic fatty liver disease (NAFLD), as well as the association between social support and adherence to diet. We also examined whether self-efficacy exerted a moderating role in these associations. QoL (SF-12), social support (MSPSS), depressive symptoms (HADS), self-efficacy (GSE), physical activity (IPAQ) and diet (MEDAS) were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…In the theory of traditional Chinese medicine, catharsis of liver Qi is helpful to inhibit the occurrence and development of depression. Indeed, a close correlation ship has been shown between depression and hepatic disorders, such as non-alcoholic fatty liver disease and liver transplantation ( Herzer et al, 2020 ; Funuyet-Salas et al, 2021 ). To verify the SX-1 protection of CUMS-induced depression-like behavior via inhibition of hepatic IL-6/JAK2/STAT3 signaling, we will repeat the present study in a mouse model of liver-specific knockout of IL-6 in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the theory of traditional Chinese medicine, catharsis of liver Qi is helpful to inhibit the occurrence and development of depression. Indeed, a close correlation ship has been shown between depression and hepatic disorders, such as non-alcoholic fatty liver disease and liver transplantation ( Herzer et al, 2020 ; Funuyet-Salas et al, 2021 ). To verify the SX-1 protection of CUMS-induced depression-like behavior via inhibition of hepatic IL-6/JAK2/STAT3 signaling, we will repeat the present study in a mouse model of liver-specific knockout of IL-6 in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating adherence to lifestyle modification recommendations for weight loss showed that depressive symptoms strongly impacted adherence to physical activity and diet recommendations. Depressive symptoms also mediated the relationship between physical quality of life, social support, and diet/exercise adherence 17 . Furthermore, those with NAFLD and stable MDD had improvement in liver enzymes after 48 weeks of standard of care compared with those with unstable MDD who had no improvement 18 .…”
Section: Impact Of Behavioral Health Care On Cld Outcomesmentioning
confidence: 94%
“…Depressive symptoms also mediated the relationship between physical quality of life, social support, and diet/exercise adherence. 17 Furthermore, those with NAFLD and stable MDD had improvement in liver enzymes after 48 weeks of standard of care compared with those with unstable MDD who had no improvement. 18 In another study, readiness to change after receiving nutritional education and guidance did not predict weight change, psychiatric symptoms did.…”
mentioning
confidence: 97%
“…This behavioural change intervention is especially useful in motivating lifestyle modification for chronic disease management, disease prevention and addictions 10 11. Several studies have reported that psychological factors and readiness for behavioural change were related to the treatment outcome of NAFLD 11 12. Thus, when managing patients with NAFLD, more attention should be focused on patients’ psychological factors and readiness for behavioural change.…”
Section: Introductionmentioning
confidence: 99%